Enhancing Urban Biodiversity: A Theory of Planned Behavior Study of the Factors Influencing Real Estate Actors’ Intention to Use Nature-Inclusive Design and Construction Concepts - Mariët A. van Haaster-de Winter; Marijke W. C. Dijkshoorn-Dekker; Thomas J. M. Mattijssen; Nico B. P. Polman (Land, 2022)
This paper presents the results of an exploration into the adoption of biodiversity-friendly practices by the real estate sector, by researching which factors determine companies’ intentions to use nature-inclusive design and construction concepts (NID). NID represents practices in which nature and building are inextricably linked when (re)designing building projects. We applied the Theory of Planned Behavior (TPB), a well-known framework for studying behavior. A telephone survey was carried out among 103 employees at different types of companies in the real estate sector. The findings showed that attitude, social norms, and perceived behavioral control are all significant explanatory variables for the intention of using NID. Perceived behavioral control is the strongest predictor. In addition, interest in NID strengthens the predictive value of perceived behavioral control. The empirical findings in this study serve as a first attempt to provide insights into the determinants of behavior in favor of using NID and, by extension, looking for drivers for change. The study was carried out in the Netherlands, but the results may be applicable or interesting to other countries as well when looking for opportunities to enhance biodiversity in urban areas or considering how the real estate sector could give substance to their vital role in spatial developments.